The end of the credential society? An analysis of the relationship between education and the labour market using big data - Brown, Phillip; Souto-Otero, Manuel (Journal of education policy, 2020)
A major focus of sociological research is on the role of the credential as a 'currency of opportunity', mediating the relationship between education and occupational destinations. However, the labour market has largely remained a 'black box' in sociological and education policy studies. This article draws on 'big data' from over 21,000,000 job adverts to explore how employers in the UK describe job requirements, with particular reference to the role of credentials. It challenges existing theories premised upon the notion that higher levels of formal education determine individual (dis)advantage in the competition for jobs. Although they have different views of the relationship between credentials, opportunity and efficiency, these theories assume that credentials largely determine occupational hiring. Our analysis suggests that formal academic credentials play a relatively minor differentiating role in the UK labour market, as the majority of employer's place greater emphasis on 'job readiness'. This raises a number of issues for sociological and policy analysis, including the future role of credentials in the (re)production of educational and labour market inequalities. Methodologically, the article highlights how the use of big data can contribute to the analysis of education, skills and the labour market.